Pengaruh Konflik Boikot terhadap Penjualan Carnation Evaporasi di Q4 2023 pada Bidang HORECA di Batam - Chelsey Monica Teo; Sonja Andarini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to analyse the effect of boycott conflict on evaporated carnation sales using sales data patterns, identify the relationship between boycott activities and evaporated carnation sales at PT Nestle Indonesia and cause an increase in sales during this boycott period. The research method used is descriptive quantitative analysis through purpose sampling technique. The results showed that the data pattern of evaporated carnation sales during the 4th quarter of 2023 for the horeca sector has a seasonal pattern that depends on major holidays in Indonesia.